2017
DOI: 10.1002/ange.201700968
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modulation of Enzyme Activity by Near‐Infrared Light

Abstract: Engineering near-infrared (NIR) light-sensitive enzymes remains ah uge challenge.Aphotothermal effectassociated method is developed for tailoring the enzymatic activity of enzymes by exposure to NIR light. An ultrasmall platinum nanoparticle was anchored in an enzyme to generate local heating upon NIR irradiation, which enhanced the enzyme activity without increasing bulk temperature.F ollowing NIR irradiation, the enzyme activity was tailored rapidly and reversibly,a nd was modulated by varying laser power de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 51 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…As a result, the complexation of these fluoroamphiphiles with BSA, an anionic protein at pH 7.4, leads to the decrease of zeta-potential of formed nanoparticles. We further labeled BSA with platinum (Pt) nanoparticles 57 . The TEM results in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the complexation of these fluoroamphiphiles with BSA, an anionic protein at pH 7.4, leads to the decrease of zeta-potential of formed nanoparticles. We further labeled BSA with platinum (Pt) nanoparticles 57 . The TEM results in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[27] NIR absorbing TTA-UC is advantageous in biological applications such as deep tissue penetration and weak photo-damage for the organism. [28][29] PdPc (OBu) 8 was proposed to use due to its intense absorbance in NIR region. When combined with a rubene emitter, NIR to visible light upconversion was able to be detected.…”
Section: The Basic Theory and Principles Of Tta-ucmentioning
confidence: 99%
“…For instance, the method of adjusting enzyme activity by NIR illumination is facile and feasible. It has been reported that platinum nanoparticles (PtNPs) within an enzyme allow local heating through the photothermal effect of the PtNPs upon NIR irradiation and consequently tailoring the enzyme activity (Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%